Self-esteem of medical students and their attitudes towards the nurse profession - Gierszon, Patrycja; Milanowska, Joanna; Łopuszańska, Urszula; Sidor, Katarzyna; Paziewska, Magdalena; Samardakiewicz, Marzena (Polish Journal of Public Health, 2020)
Introduction. The profession of a nurse is next to the medical profession, one of the pillars of medical care in Poland and in the world. In recent years, the need to see the importance of this profession and the responsibility associated with it, both by the public and the doctors, is increasingly underlined. Aim. The research carried out is an attempt to answer the question, what attitudes towards nurses are shaped by future doctors already during the studies and what influence on students’ self-esteem on these attitudes. Material and methods. The research was conducted among 89 students of the medical faculty, Medical University in Lublin in April 2018. A questionnaire of own authorship was used, constructed on the basis of descriptive research carried out by Maik M. et al and the Rosenberg Self-Assessment Questionnaire (SES). The obtained results were subjected to statistical analysis using the STATISTICA program, version 13.1. Result. The vast majority of medical students (80%) believe that the role of a nurse is underestimated both in society and in the medical community. Students think that this work requires sacrifice and constant vigilance. Students who have encountered nursing staff notice symptoms of burnout in some of them, such as depersonalization of patients (56%). However, most of them (60%) think that this is ungrateful work and often interferes with family life. Students do not agree that the nurse should always be smiling and optimistic (75%). She values her features such as patience, good organization of time (86%) and ability to cooperate with doctors (91%). Most of students think that a nurse is a partner of a doctor (73%), while almost half (49%) of them see imperfections in cooperation both professional groups, resulting from the lack of mutual respect (64%). Students notice the commitment and hard work performed by nurses (70%), and also, although to a lesser extent, they appreciate their knowledge (56%). Conclusion. Appreciation of the nurse’s role on the part of doctors seems to be particularly important due to the need for cooperation of medical staff. The quality of cooperation between the interdisciplinary team and, consequently, the quality of care and medical care depends to a large extent on the mutual respect, understanding and correct communication between these professional groups.